Pros and cons for the medical age assessments in unaccompanied minors: a mini-review - De Sanctis, Vincenzo; Soliman, Ashraf T.; Soliman, Nada A.; Elalaily, Rania; Di Maio, Salvatore; Bedair, Elsaid M. A.; Kassem, Islam; Millimaggi, Giuseppe (Acta Biomedica Atenei Parmensis, 2016)
Unaccompanied minors refer to immigrants who are under the age of 18 and are not under the care of a parent or legal guardian. Age assessment is used in Europe mainly to establish whether or not an individual is under 18 years of age and therefore eligible for protection under the United Nations’ Convention on the Rights of the Child (UN - CRC). EU Member States use a combination of techniques to determine the age of a minor and to certify minor status, including interviews and documentation, physical examinations (anthropometric assessment; sexual maturity assessment; dental observation); psychological and sociological assessment; radiological tests (carpal, dental or collarbone x-rays). All such techniques are criticized as they are often arbitrary, do not take into account ethnic variations, and are based on reference materials that are outdated, invasive and may procure harm to the individuals whose age is assessed. They also generate a margin of error that makes them inaccurate to use. There is a debate about the risks and ethics associated with the use of X-rays for non-medical purposes versus the benefits of more accurate age assessments in the interest of justice. It appears that in European countries many individuals carrying out age assessment do not have sufficient training or are not sufficiently independent enough to be carrying out such assessments. Moreover, there is a lack of standardized approach between countries or even within the same country. Only some countries clearly indicate a margin of error in the results of age assessment examinations but there is no consensus – within and among countries – about the width of such margins in relation to each exams applied. It has been advised that the expert report should give the degree of age probability to allow Magistrate to interpret the age assessment results on the ‘balance of probabilities’ and give the detainee the right to the rule of the ‘benefit of the doubt’. It also addresses concerns rested in the convention of the Rights of the Child.